Learning on demand: dynamic creation of customized, coherent eLearning experiences - Santos, O. (2012)
This paper presents a conceptual model concerning automatic creation of coherent eLearning experiences through dynamic aggregation of heterogeneous learning objects. The model uses detailed user profiles as the main key to create customized learning content, tailored to each user’s needs, preferences and skills. Aggregation of heterogeneous learning objects may result in a very incoherent learning sequence. Therefore, the model incorporates a method to improve the learning coherence of the generated course. The compromise between customization and coherence is fully adjustable from maximum coherence to maximum customization.